Taxonomic Distribution of FosB in Human-Microbiota and Activity Comparison of Fosfomycin Resistance - Song, Ziwei; Wang, Xue; Zhou, Xingchen; Jiang, Su; Li, Yuanyuan; Ahmad, Owais; Qi, Lianwen; Li, Ping; Li, Jing (Frontiers in Microbiology, 2019)
FosB, a Mg2+ dependent thioltransferase, confers antibiotic resistance to fosfomycin through enzymatic drug inactivation. Among all antibiotic resistance proteins in Antibiotic Resistance Genes Database and Comprehensive Antibiotic Resistance Database, FosB is within 5% of the most number of ARPs identified in Human Microbiome Project reference database but mainly distributed in limited genera, i.e., 122 of total 133 FosB homologues are found from Bacillus and Staphylococcus. Furthermore, these FosB sequences could be divided into three clusters based on their phylogenetic relationship, i.e., two groups of FosB were mainly from Bacillus, and another was mainly from Staphylococcus. Finally, we confirmed that FosB from the group of Staphylococcus presented the highest ability of resistance to fosfomycin by in silico and in vitro comparisons. In summary, this study elaborates the specific taxonomic characters and resistant abilities of FosB in human microbiota, which might help in developing more promising fosfomycin-like antibiotics. Keywords: FosB, fosfomycin, antibiotic resistance proteins, gut microbiota, Staphylococcus